Hosoya entropy analysis of some fullerene structures - Ali N. A. Koam; Muhammad Faisal Nadeem; Ali Ahmad; Abdullah Ali H. Ahmadini; Bahreselam Sielu Abraha; Ibtisam Masmali (Discover Nano)
Abstract This study examines the structural complexity of fullerene graphs using Hosoya entropy as a measure. The entropy values were calculated for various fullerene structures, including $$F^s_{3,1},$$ F 3 , 1 s , $$F^s_{4,2}$$ F 4 , 2 s and fullerenes ranging from C20 to C100.The relationship between the size of the fullerenes and the entropy is intuitively clear: the larger the fullerenes, the higher the value of entropy because of increased structural complexity and diversity of equivalence classes. Smaller fullerenes, like C20, have lower entropy, a consequence of their simpler and more symmetrical molecular structure. These findings provide theoretical insights into structural intricacies of fullerenes and their possible applications in material science and nanotechnology.